Shifts in religiosity across cohorts in Europe: A multilevel and multidimensional analysis based on the European Values Study - Molteni, Francesco (Social compass, 2018)
Religious change continues to be a controversial topic that involves both theoretical and methodological issues. As to the European context, the main dispute is between secularization and individualization theory, especially considering the believing without belonging' thesis. This article will tackle this dispute given these three choices: firstly, we assume that cohort replacement is the main driver of religious change; secondly, religious tradition has to be taken fully into account to explain religious change; thirdly, we consider religiosity as a complex phenomenon that requires a multidimensional approach. Results from a multilevel multiple responses model based on EVS (European Values Study) data show that practice is declining across cohorts in all the countries whereas trends for belief and self-definition diverge only for Eastern Orthodox countries. Depending on the interpretation, such exception seems supporting rather than undermining the believing without belonging' theory.